2022
DOI: 10.1039/d2cp03624j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of cold welding of nanoporous amorphous alloys: effects of welding conditions and microstructures

Yuhang Zhang,
Lei Su,
Jianfei Xu
et al.

Abstract: Cold welding behaviors of nanoporous amorphous alloys investigated by molecular dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 89 publications
(146 reference statements)
0
9
0
Order By: Relevance
“…It is observed that the tensile and compressive responses are asymmetric, which is attributed to the surface effects of nanoporous metals. 28,29,[34][35][36][37] At the same absolute strain, the tensile stress is larger than the compressive stress. The stress amplitude gradually increases with increasing the cycle number.…”
Section: Fundamental Fatigue Responsesmentioning
confidence: 99%
See 4 more Smart Citations
“…It is observed that the tensile and compressive responses are asymmetric, which is attributed to the surface effects of nanoporous metals. 28,29,[34][35][36][37] At the same absolute strain, the tensile stress is larger than the compressive stress. The stress amplitude gradually increases with increasing the cycle number.…”
Section: Fundamental Fatigue Responsesmentioning
confidence: 99%
“…Because the orientations of ligaments are random, the rotation of ligaments and plastic hinge formation are the major deformation modes of the NPMG upon axial loading. 28,29,50,51 This rotation of ligaments during tensile loading makes them tend to align with the tensile direction. After monotonic tensile loading, the macroscopic lateral dimensions of the structure reduce significantly.…”
Section: Underlying Physical Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations